The Measurements of Aerodynamic Effects in Tunnels on the Czech Railway Network (Current Problems in Rail Vehicles, 2025)
The article presents aerodynamic measurements in tunnels on Czech railway network whose main task was to demonstrate effect magnitudes at speeds of 160 to 200 km/h and to analyse the results in relation to new projects of lines. There are presented examples of measured pressure changes and airflow speeds on the fixed position inside tunnel or pressure changes on the surface of running train. Further there are shown pressure loads acting on the vehicle and passenger pressure comfort for such train speeds. Finally, there are summarised related requirements on vehicles that comprise important part of design and operation on new lines in the Czech Republic with the speed of 200 km/h.
Keywords: aerodynamics; tunnels; railway vehicles; measurement; pressure changes